2009
DOI: 10.2320/matertrans.mbw200807
|View full text |Cite
|
Sign up to set email alerts
|

Grain-Size Refinements of Cu-3 mass%Ti Alloys by HDDR Treatments in Correlating with Their Electrical and Mechanical Properties

Abstract: The present paper describes the grain size refinements of Cu-3 mass%Ti alloys by hydrogen heat-treatment of so-called HydrogenationDisproportionation-Desorption-Recombination (HDDR) process. During hydrogenation process, the disproportionation reaction occurred with forming of Ti hydrides in the alloy. With decomposition of Ti hydrides by the subsequent desorption process, Ti resolved into Cu matrix. In consequence, the original solid solution phase of the alloys formed. This means that the HDDR phenomena coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…For Cu solidsolution alloy in Cu-Ti system, Vegard's law could be applied, in which the lattice constants are proportional to Ti amount in fcc matrix. This reduction of lattice constants might be due to decrement of Ti content in copper-matrix, in probably forming TiH 2 during hydrogen heat-treatment [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Cu solidsolution alloy in Cu-Ti system, Vegard's law could be applied, in which the lattice constants are proportional to Ti amount in fcc matrix. This reduction of lattice constants might be due to decrement of Ti content in copper-matrix, in probably forming TiH 2 during hydrogen heat-treatment [7].…”
Section: Resultsmentioning
confidence: 99%
“…However, hydrogen had been regarded as harmful element such as inducing hydrogen-embrittlement in metals. Recently, the new attempts to find the useful function of hydrogen have attracted much attentions since hydrogen introduces the unexpected function in materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The present paper reviews the useful function of hydrogen recently found in the materials, in relation to drastically increase their properties, in adding newly obtained results.…”
Section: Introductionmentioning
confidence: 91%
“…That means all samples could hydrogenate under the condition. In our previous work, it was found that the Cu-3mass% alloy decomposed to Cu-matrix phase, Ti-hydride (TiH~2) and D1a (Cu 4 Ti) phase [11]. Figure 2 shows nominal stress of the corresponding alloys for as-rolled state, after hydrogenation or after annealing under Ar atmosphere at 350°C for 48h.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we also reported the grain size refinements of Cu-3mass%Ti alloys by hydrogen heat-treatment of HDDR process [11]. The alloy is commercially available, and has been widely used for high-strength electrical conducting materials such as lead frames and connectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation